Teacher Competence in the Use of ChatGPT for Developing Learning Media in Vocational High Schools - Tri Aji, Purno; Aris Nasuha; Dessy Irmawati; Moh Alif Hidayat Sofyan; Ahmad Taufiq Musaddid (International Journal of Community Service Learning, 2024)
ChatGPT technology opens up great education opportunities, especially in supporting the development of educator competencies needed in the 21st century. However, teacher competency in utilizing Artificial Intelligence (AI) technology is still low. As a result, existing learning media are not optimal in presenting engaging and interactive digital teaching materials according to the needs of students in the era of education 4.0. This community service aims to improve the competence of vocational high school teachers in using ChatGPT and AI applications for the development of learning media. This study involved 60 teachers from various fields. The methods used were lectures, discussions, and direct practice with online assistance. Teachers were trained to create interactive teaching materials using ChatGPT and other AI applications. The data analysis technique used qualitative descriptive analysis. The post-test results showed a significant increase in teacher competency in using AI applications, with an average score above 4 out of 5 in key aspects such as material usefulness and skill development. The activity results showed increased teachers' ability to utilize AI technology to create digital-based learning media, such as learning videos and interactive teaching materials. This activity significantly improves the quality of the learning process in vocational high schools. This training is expected to optimize teachers' digital skills to face challenges in the era of education 4.0.